Destinação do Lixo na zona rural, Comunidade Aracuri - Lago Grande, Santarém, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
This work aimed to investigate possible solutions to the problem of the absence of garbage collection in a rural Aracuri community, located in the municipality of Santarém. In addition, sensitize students, residents and society in general to the problems caused by the disposal of rural wastes in inappropriate places, such as: near the residences; streams, rivers and lakes, open skies and demonstrate the absence of public policies to contain the advances of polluting agents produced by man in rural communities, which increasingly accelerates environmental degradation processes in the field. The literature search enabled some solutions such as the recycling of some materials.
Keywords: resíduos sólidos; zona rural; meio ambiente; População amazônica; CNPQ:: CIÊNCIAS BIOLÓGICAS